Implementasi Penguatan Pendidikan-Karakter (PPK) Kitab Al-Akhlak-Lil-Banin Di PP Hidayatul Insan Palangka Raya - Hunainah Hunainah; Ahmad Syarif; Desy Nur Hikmah; Sabrianysah Sabrianysah (At-Ta'lim : Media Informasi Pendidikan Islam, 2022)
Abstract: Implementation of Strengthening Character Education (PPK) from Kitab al-Akhlak lil Banin at PP Hidayatul Insan Palangka Raya.Education is a strategic indicator of the progress of a nation. Various cases occurred in Palangka Raya city and others still indicate strongly that the Character Education Strengthening Program requires synergy from various parties, not only the government. This research aims to analyze 1) the main content of PPK of Al-Akhlaq li al-Banin and 2) the implementation of the Character Education Strengthening Program for students based on the book of Al-Akhlak Lil Banin. The findings not only become the importance of this research but also the dissemination to the society (particularly the students) of Central Kalimantan in supporting the character education strengthening programs. In addition, it is expected to spark creativity from both state and private schools to succeed in the program. This research takes a qualitative approach with critical and descriptive analysis methods. Some of the findings from this study are as follows. First: The study of the book Al-Akhlaq li al-Banin has long been carried out in the Islamic boarding school, and now it is included in the intracurricular activities. For this reason, the evaluation of this book is carried out in two ways: cognitive and implementation. The second finding, KDP teaching is carried out by planting and qudwah by all stakeholders. The third finding is the impact of implementing PPK such as being more disciplined and religious, being able to appreciate solidarity and mutual cooperation in maintaining conduciveness of security, cleanliness and tranquility. The evaluation of the implementation of PPK is the character that has been trying to be built can be lost even when the students return home, while the home environment does not apply positive character. For this reason, the power of qudwah must be consciously implemented by students and spread again within the family and community.Abstrak: Implementasi Penguatan Pendidikan-Karakter (PPK) dari-Kitab-al-Akhlak-lil-Banin pada PP Hidayatul Insan Palangka Raya.Sektor pendidikan menjadi indikator startegis kemajuan suatu bangsa. Pelbagai kasus yang terjadi di Palangka Raya maupun di kota lain masih mengindikasikan dengan kuat bahwa Program Penguatan Pendidikan Karakter memerlukan sinergi berbagai pihak, tidak hanya pemerintah. Penelitian-ini-bertujuan-untuk-mengetahui: 1) analisa muatan utama PPK dari Al-Akhlaq li al-Banin; 2) Bentuk implementasi Program Penguatan Pendidikan Karakter dari para santri berdasarkan kitab Al-Akhlak Lil Banin. Hasil penggalian tidak hanya untuk kepentingan riset, namun disebarluaskan ke masayarakat, khususnya masyarakat Kalimantan Tengah dan pada santri agar dapat dimanfaatkan sebagai sarana penunjang program penguatan pendidikan karakter, juga memantik kreatifitas para sekolah negeri maupun swasta dalam upaya meramaikan program penguatan pendidikan karakter. Penelitian ini menggunakan pendekatan kualitatif, dengan metode analisis kritis dan deskriptif. Beberapa hasil temuan dari penelitian ini adalah sebagai berikut. Pertama: Pengkajian kitab Al-Akhlaq li al-Banin telah lama dilakukan di dalam pondok, dan kini masuk dalam intrakulikuler. Untuk itu, evaluasi dari kitab ini dilakukan dengan dua cara: kognitif dan uji implementasi. Temuan kedua, pengajaran PPK ini dilakukan dengan penanaman dan qudwah oleh segenap pemangku kebijakan. Temuan ketiga yaitu dampak pelaksanaan PPK seperti lebih disiplin dan religius, dapat menghargai waktu solidaritas dan gotong royong dalam menjaga kondusifitas keamanan, kebersihan, dan ketenangan. Evaluasi dari implementasi PPK ini adalah karakter yang telah berusaha dibangun bisa hilang bahkan bilamana saat santri kembali ke rumah, sedangkan lingkungan rumah tidak menerapkan karakter positif. Untuk itu kekuatan qudwah ini harus secara sadar diimplementasikan santri dan ditebarkan kembali di lingkungan keluarga dan masyarakat.